Analysis and Evaluation of The Electromagnetic Field Pollution in Marmara University Başıbüyük Campus Using Gas Discharge Visualization TehniqueAccording to Different Weather Conditions - AKAR, AYNUR; BÖCEKÇİ, VEYSEL GÖKHAN (My University, 2020)
The continuous development of technology and, accordingly, people's interest in technological devices is increasing. Electricpowered devices generate electricity and magnetic fields. The intensity of electric and magnetic fields is restricted by international organizations and limit values by Turkey's Information Technologies and Communication Authority (BTK). The values of the electromagnetic field generated by the base stations are monitored by the BTK. The limit values determined by the BTK are more stringent than those set by international organizations. The intensity of the electromagnetic field varies according to the distance and power to the system. In this study, electromagnetic field pollution in Marmara University Başıbüyük Campus was analyzed periodically and according to different weather conditions. Measurements were performed at 19 different points and the results were mapped. SRM 3006 model selective radiation meter was used in the measurement. Measurement results were compared with international limit values and evaluated. The limit value determined by international organizations for the environment is 61 V/m and the limit value determined by BTK is 42 V/m. 12-day average electric field is 1.53 V/m for periodical measurements. The average electric field in sunny weather is 1.9 V/m, 1.28V/m in rainy weather and 1.39V/m in cloudy weather. Gas Discharge Visualization technique was used to observe the possible changes in the energy and stress situation of the different electromagnetic field pointswithin the campus. Energy and stress measurement with this technique was performed with Bio-well device. According to the measurement results, no change in stress and energy status was observed.

Teknolojinin sürekli gelişimine bağlı olarak insanların teknolojik cihazlara olan ilgileri artmaktadır. Elektrik ile çalışan cihazlar elektrik ve manyetik alan üretirler. Elektrikve manyetik alan yoğunlukları uluslararası kuruluşlar ve Türkiye Bilgi Teknolojileri ve İletişim Kurumu (BTK) tarafından sınırlandırılmaktadır. Baz istasyonları tarafından üretilen elektromanyetik alan değerleri BTK tarafından takip edilmektedir. Ayrıca BTK tarafından belirlenen sınır değerler uluslararası kuruluşlara göre daha katıdır. Elektromanyetik alanın yoğunluğu, sisteme olan mesafe ve gücüne göre değişmektedir. Bu çalışmada, Marmara Üniversitesi Başıbüyük Kampüsü’ndeki elektromanyetik alan kirliliği periyodik olarak ve farklı hava koşullarına göre analiz edilmiştir. Ölçümler 19 farklı noktada yapılmıştır ve haritalandırılmıştır. Ölçümde SRM 3006 model selektif radyasyon ölçer cihazı kullanılmıştır. Ölçüm sonuçları uluslararası limit değerlerle karşılaştırılmıştırve değerlendirilmiştir. Uluslararası kuruluşlar tarafından ortam için belirlenen sınır değer 61 V/m, BTK tarafından belirlenen sınır değer ise 42 V/m’dir. 12 günlük periyodik ölçümlerin ortalama elektrik alan değeri 1,53 V/m’dir. Güneşli havalarda ortalama elektrik alan 1,9 V/m, yağışlı havalarda 1,28 V/m ve bulutlu havalarda 1,39 V/m’dir. Kampüs içindeki farklı elektromanyetik alan noktalarının enerji ve stres durumlarındaki olası değişikliklerini gözlemlemek için Gaz Boşalım Görselleştirmesi tekniği kullanılmıştır. Bio-well cihazı ile bu teknik kullanılarak stres ve enerji ölçümü yapılmıştır. Ölçüm sonuçlarına göre stres ve enerji durumlarında herhangi bir farklılık gözlenmemiştir.
Marmara Üniversitesi Başıbüyük Kampüsü'ndeki Elektromanyetik Alan Kirliliğinin Farklı Hava Koşullarına Göre Gaz Boşalım Görselleştirmesi Tekniği Kullanılarak Analizi ve Değerlendirilmesi